Red Trauma: Aleksander Kobzdej’s Informel and the Challenge of Stalinist Past - Wiktor Komorowski (Janeway JS, 2018)
This article investigates the relation between Socialist realism and Polish ‘matter painting’. By taking a closer look at the use of red hue developed by Aleksander Kobzdej for his informel compositions, it attempts to uncover psychological challenges Polish post-war artist had to face trying to emancipate from the Socialist tradition. A major work that only distantly approaches the topic of psychological stigma came to light along with the exhibition Nowoczesni a Socrealizm, which took place at the Starmach Gallery in Krakow in 2000. A more developed argument in this matter can be found in Tomasz Gryglewicz’s paper ‘Co zawdzięcza sztuka polska PRL-owi?’ in which he pointed out that the success of Polish ‘matter painting’ was based on the fact that Polish artists managed to preserve the pre-war ideas of Polish structuralism and colourism from the trauma of war and Stalinism. This alleged success became the input of Polish ‘matter painting’ in the development of European post-war art. This article offers an alternative argument to the one presented by Gryglewicz as it points to the fact that the unique character of the Polish art of the 1960s comes not from the ability to rebuild the pre-war avant-garde tradition, but rather from the ability to challenge the distress caused by the Stalinist past.